Acculturation attitudes and adaptation among portuguese immigrants in Germany: integration or separation - Félix Neto (2005)
This study aims to understand preferences in acculturation strategies among Portuguese immigrants in Germany. The sample comprised 118 adults (mean age 41.9 years; SD 11.5). The average length of residence in Germany was 20.4 years (SD 9.1). Responses to the questionnaire revealed that integration was the most preferred acculturation strategy. Subjects who adopted an integration strategy manifested greater acculturation experience with German culture than those who adopted separation. Subjects who chose integration and separation strategies did not differ in their degree of cultural maintenance. Immigrants who chose an integration mode experienced lower levels of social adaptation difficulties than those who favoured a separation mode, but these two strategies did not reveal different levels of psychological adaptation. Understanding the complex relationships between demographic, intercultural and psychosocial adjustment factors, and acculturation strategies can help social scientists develop and apply adequate intervention strategies and give suggestions for the development of adequate sociopolitical acculturation programmes.